RECONSTRUCTION OF BASIC KNOWLEDGE ON LEARNING BIPA FOR DEVELOPING PROFESSIONALISM OF BIPA TEACHERS - Suyitno, Imam (IJRDO- Journal of Educational Research, 2017)
This study aims to describe aspects of learning Indonesian for foreign students (BIPA) thatneed to be understood by someone who will teach BIPA. The basic knowledge can beutilized by the teacher to select teaching-learning strategies and teaching materials thatrequired by BIPA students. To gain those understanding, this study effort to collect dataabout an information on the implementation of learning BIPA from the real class ofteaching-learning BIPA. By using a qualitative approach with a model of ethnographicanalysis, the study obtain findings that (a) foreign students studying BIPA hascharacteristics that different both in terms of learning styles and cultural backgrounds, (b)the implementation of learning BIPA more emphasis on the communicative consideringlearning styles of BIPA students, (c) learning approach of BIPA need to consider to thenorms of pedagogical of language learning for adult learners so that the topic of languageteaching materials must be selected based on the needs of adults in communication, and (d)the cultural aspects in the form of cultural knowledge, cultural behaviors, and culturalobjects made as teaching material in learning BIPA by using a variety of learningtechniques